Establishment, optimization and validation of a fluorescence polarization-based high-throughput screening assay targeting cathepsin L inhibitors - Wenwen Zhou; Baoqing You; Xiaomeng Zhao; Shuyi Si; Yan Li; Jing Zhang (SLAS Discovery, 2024)
Cathepsin L (CTSL), a lysosomal cysteine proteinase, is primarily dedicated to the metabolic turnover of intracellular proteins. It is involved in various physiological processes and contributes to pathological conditions such as viral infection, tumor invasion and metastasis, inflammatory status, atherosclerosis, renal disease, diabetes, bone diseases, and other ailments. The coronavirus disease 2019 (COVID-19), with its rapid global spread and significant mortality, has been a worldwide epidemic since the late 2019s. Notably, CTSL plays a role in the processing of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein, providing a potential avenue to block coronavirus host cell entry and thereby inhibit SARS-CoV-2 infection in humans. In this study, we have developed a novel method using fluorescence polarization (FP) for screening CTSL inhibitors in a high-throughput format. The optimized assay demonstrated its appropriateness for high-throughput screening (HTS) with a Z-factor of 0.9 in a 96-well format. Additionally, the IC50 of the known inhibitor, Z-Phe-Tyr-CHO, was determined to be 188.50 ± 46.88 nM. Upon screening over 2000 small molecules, we identified, for the first time, the anti-CTSL properties of a benzothiazoles derivative named IMB 8015. This work presents a novel high-throughput approach and its application in discovering and evaluating CTSL inhibitors.